2022
DOI: 10.1002/adma.202109718
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrahigh‐Flux Nanoporous Graphene Membrane for Sustainable Seawater Desalination using Low‐Grade Heat

Abstract: MD) is a simple process that utilizes heat to drive vapor to pass through a porous hydrophobic membrane and obtains clean and fresh water in the permeate, while liquid water is blocked by surface hydrophobicity. [2] The potential of using lowgrade heat has made MD a promising low-cost and sustainable water desalination technology. [3] MD is also a key technology in many zero-discharge sustainable processes because the "last-mile" of such processes often involves a high-salinity water solution that is failed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…5 ) and limitations in how thin membranes can be made because of wetting constraints. We note that transport resistances at the liquid-vapor interface have only recently been defined, and a few recent studies have shown water permeabilities in air-filled membranes that exceed those theoretically possible based on current transport models ( 20 , 21 , 25 , 95 , 96 ). Thus, it may be possible to create high-permeability air-filled membranes that can offer comparable water permeabilities to RO membranes without sacrificing selectivity.…”
Section: Which Applications Are Different Membrane Types and Driving ...mentioning
confidence: 85%
“…5 ) and limitations in how thin membranes can be made because of wetting constraints. We note that transport resistances at the liquid-vapor interface have only recently been defined, and a few recent studies have shown water permeabilities in air-filled membranes that exceed those theoretically possible based on current transport models ( 20 , 21 , 25 , 95 , 96 ). Thus, it may be possible to create high-permeability air-filled membranes that can offer comparable water permeabilities to RO membranes without sacrificing selectivity.…”
Section: Which Applications Are Different Membrane Types and Driving ...mentioning
confidence: 85%
“…[83][84][85] Tremendous research efforts have been devoted to the development of novel membrane materials and/or configurations, aiming at facilitating the practical application of MD technology. 85,86 For instance, novel MD membranes with ultrahigh vapor permeabilities have been fabricated using covalent organic frameworks or ultrathin nanoporous graphene, 87,88 and solar or electricity driven MD systems have been developed to improve the energy efficiency. 89,90 Despite these technological innovations, MD is still an emerging technology under lab-scale development.…”
Section: Desalination For Sustainable Water Productionmentioning
confidence: 99%
“…Lu et al [ 67 ] developed a new process for the preparation of ultrahigh throughput nanoporous graphene membranes, which eliminates the need for secondary drilling and transfer processes after membrane synthesis. The resulting graphene film provides a concise and fast transport path for water vapor.…”
Section: Photothermal Materials For Solar Interfacial Evaporationmentioning
confidence: 99%